2007
DOI: 10.1016/j.virol.2007.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of UL24 in herpes-simplex-virus-1-induced dispersal of nucleolin

Abstract: UL24 of herpes simplex virus 1 is important for efficient viral replication, but its function is unknown. We generated a recombinant virus, vHA-UL24, encoding UL24 with an N-terminal hemagglutinin tag. By indirect immunofluorescence at 9 h post-infection (hpi), we detected HA-UL24 in nuclear foci and in cytoplasmic speckles. HA-UL24 partially co-localized with nucleolin, but not with ICP8 or coilin, markers for nucleoli, viral replication compartments, and Cajal bodies respectively. HA-UL24 staining was often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 57 publications
5
83
2
Order By: Relevance
“…HSV-1 strains were propagated and titrated on Vero cells as described previously (Lymberopoulos & Pearson, 2007). The HSV-1 strains KOS, UL24XG (Jacobson et al, 1998) and tkLTRZ-1 (Davar et al, 1994) were originally provided by D. M. Coen (Harvard Medical School, Boston, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HSV-1 strains were propagated and titrated on Vero cells as described previously (Lymberopoulos & Pearson, 2007). The HSV-1 strains KOS, UL24XG (Jacobson et al, 1998) and tkLTRZ-1 (Davar et al, 1994) were originally provided by D. M. Coen (Harvard Medical School, Boston, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Transient expression of UL24 homologues from murine gammaherpesvirus 68, Kaposi's sarcoma-associated virus, human cytomegalovirus and HSV-1 induce a G2M cell cycle block (Nascimento & Parkhouse, 2007;Nascimento et al, 2009). UL24 is required for the HSV-1-induced dispersal of nucleolin (Lymberopoulos & Pearson, 2007) and the N-terminal region of UL24 is sufficient to induce the redistribution of this nucleolar protein (Bertrand & Pearson, 2008). More recently, we found that residues corresponding to the putative catalytic domain are especially important for the ability of UL24 to induce this modification of nucleoli.…”
Section: Introductionmentioning
confidence: 99%
“…Lytic induction also caused redistribution of nucleolin; rather than being confined to a discrete dot, nucleolin within cells expressing ZEBRA was visibly dispersed. Dispersal of nucleolin also occurs during lytic infection of HSV-1 and is mediated by the UL24 protein (51,52). In cells transfected with Z(R183E), nucleolin was not recruited to aggresomes (supplemental Fig.…”
Section: Z(k178d) Z(r179e) Z(r183e) and Z(r190e) Mutants Are Partimentioning
confidence: 98%
“…These findings suggest that viral replication compartment formation may be responsible for the chromatin marginalization observed. A recent study has shown the involvement of the HSV-1 U L 24 protein in the dispersal of nucleolin (Lymberopoulos and Pearson, 2007). It remains unclear as to whether the alteration of nucleolin is an active process or a secondary consequence of replication compartment formation and/or chromatin marginalization.…”
Section: Nucleolar Dynamics Are Influenced By Hsv-1 Infection During mentioning
confidence: 99%